Why liberalism works : how true liberal values produce a freer, more equal, prosperous world for all - McCloskey, Deirdre N. (Yale University Press, 2019)
An insightful and passionately written book explaining why a return to Enlightenment ideals is good for the world. The greatest challenges facing humankind, according to Deirdre McCloskey, are poverty and tyranny, both of which hold people back. Arguing for a return to true liberal values, this engaging and accessible book develops, defends, and demonstrates how embracing the ideas first espoused by eighteenth-century philosophers like Locke, Smith, Voltaire, and Wollstonecraft is good for everyone. With her trademark wit and deep understanding, McCloskey shows how the adoption of Enlightenment ideals of liberalism has propelled the freedom and prosperity that define the quality of a full life. In her view, liberalism leads to equality, but equality does not necessarily lead to liberalism-and the fixation of the left on inequality is counterproductive. Liberalism is an optimistic philosophy that depends on the power of rhetoric rather than arms and on ethics, free speech, and facts for us to thrive. -- Provided by publisher.